Characteristics of Silicon Photomultiplier at cryogenic temperatures - Kiilerich, Tom (My University, 2024)
We are conducting optical 1S-2S spectroscopy of magnetically trapped atomic hydrogen at ultra-low temperatures. For this an optical diagnostic scheme which is operational in a dilution refrigerator at temperatures below 1 K is required. In this thesis we discuss the theory behind Silicon Photomultipliers (SiPMs) and how their properties are affected at cryogenic temperatures. We describe the operation and characterization of SiPMs at various cryogenic temperatures, down to 180 mK. We show the temperature dependence of the signal shape, breakdown voltage, microcell capacitance and gain, dark count rate and photon detection efficiency, concluding that SiPMs can be effectively used at ultra-low temperatures with sensitivity at the single photon level. Below 40 K we observed a secondary breakdown in the SiPM due to a quantum tunneling effect, which set an upper limit for the bias voltage operating region. Assessment of the damage to the SiPM due to thermal cycles shows that the SiPM can withstand multiple cooling cycles without losing its efficiency.
Keywords: Silicon Photomultiplier, SiPM, light detection, single photon detection, optical spectroscopy, cryogenic temperatures